Cisco Systems : developing a human capital strategy (A) - Chatman, Jennifer; O'Reilly, Charles A. (London : SAGE Publications Ltd, 2017)
Like many technology organizations in the late 1990s, Cisco was booming. It grew so quickly, in fact, that it was bringing in up to 1,000 new employees each month. Cisco's solution was to acquire talent by buying small firms, topping out in one year with 24 separate acquisitions. However, in 2000 the dot-com bubble burst and Cisco quickly realized that it had another human capital challenge on its hands: How to develop, rather than hire, the strategic thinkers and leaders needed for the future. This case study explores the challenges facing Mary Eckenrod, Ciscos Vice President of Worldwide Talent, in developing a new human capital strategy to identify and develop leaders from within the companyand to do this in a company with no tradition of developing people internally. How can Cisco move from a "buy" to a "make" human capital strategy? The lessons from this case provide a template that other organizational leaders can use in managing organizations through various stages of evolution and different types of growth.
Originally published in Chatman, J., & OReilly, C. (2004). Cisco Systems: Developing a human capital strategy (A). The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; Cisco Systems, Inc; electronic books; Human capital -- Case studies; Organizational behavior -- Case studies